Community Service for Improving of Learning Pronounce Silent Letters Thought Youtube Content by Channel Youtube For 12th Smk Kesehatan Rambah Samo - Darmayanti, Yesi; Amanda, Vivi; Ria Ningsih, Asih (CEMARA: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This study examines the impact of utilizing YouTube content on enhancing twelfth-grade students’ pronunciation of English silent letters at SMK Kesehatan Rambah Samo. Employing a quasi-experimental design, two groups were compared: an experimental group that was taught through YouTube videos and a control group that was taught using traditional methods. Data were collected using pre-tests and post-tests administered to both groups, each consisting of 30 students. The findings revealed that the experimental group achieved a significant improvement in pronunciation performance (t = 9.84, p < 0.05) compared to the control group (t = 2.11, p > 0.05). The independent t-test also indicated a significant difference in gain scores (t = 5.43, p < 0.05), with a large effect size (Cohen’s d = 1.10). These results demonstrate that YouTube-based learning provides multimodal input, visual, auditory, and textual, that enhances learners’ ability to recognize and correctly pronounce words containing silent letters such as debt, subtle, climb, and honest. The study concludes that integrating authentic YouTube materials into pronunciation instruction significantly improves students’ phonological awareness and fosters autonomous learning compared to traditional classroom methods.